2009
DOI: 10.1603/029.102.0330
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Optimum Pheromone Release Rate for Attraction of <I>Chilo suppressalis</I> (Lepidoptera: Pyralidae)

Abstract: Traditional chemical control against Chilo suppressalis Walker is currently being replaced in Spain by new methods based on pheromones. A key step to improve the efficacy of these methods is the determination of the optimum pheromone release rate, which is still uncertain for this pest. In this work, the pheromone release profile and the field performance of a new mesoporous dispenser was compared with a standard commercial dispenser. For this purpose, pheromone loads were extracted from field-aged dispensers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
2
22
0
2
Order By: Relevance
“…Similar behavior was observed for rice leaffolder moth, Cnaphalocrocis medicinalis (Guenée) (Kawazu et al, 2004). Vacas et al (2009b) found decreasing catches of Chilo suppressalis (Walker) below and above an optimal release rate of 34 µg per day. And Jactel and coworkers (2006) found an asymptotic increase response of catches of pine processionary moth (Thaumetopoea pytiocampa Denis & Schiffermüller) according to increasing doses of its pheromone from 0.5 to 20 mg, with 95% of maximum catch obtained with the 10-mg dosage.…”
Section: Vi4 Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Similar behavior was observed for rice leaffolder moth, Cnaphalocrocis medicinalis (Guenée) (Kawazu et al, 2004). Vacas et al (2009b) found decreasing catches of Chilo suppressalis (Walker) below and above an optimal release rate of 34 µg per day. And Jactel and coworkers (2006) found an asymptotic increase response of catches of pine processionary moth (Thaumetopoea pytiocampa Denis & Schiffermüller) according to increasing doses of its pheromone from 0.5 to 20 mg, with 95% of maximum catch obtained with the 10-mg dosage.…”
Section: Vi4 Discussionsupporting
confidence: 73%
“…However, only few studies determined the optimal release rate of attractants (de Groot & DeBarr, 1998;Cross et al, 2006;Vacas et al, 2009b). As mentioned above, catches do not always increase with increasing pheromone doses.…”
Section: Vi4 Discussionmentioning
confidence: 99%
See 3 more Smart Citations